Comportamento de blocos estruturais de concreto com diferentes agregados sob altas temperaturas - Medeiros, Wallison Angelim (Universidade Federal de São Carlos, 2022)
The present work aims to investigate, in laboratory, of structural concrete blocks submitted to high temperatures to contribute with relevant information for the design of structural masonry in a fire situation. Since Brazil still does not have a national standard for masonry design in a fire situation, a first study was carried out, applying international standards for the Brazilian context. However, this approach must be carried out with caution, as there are significant differences in materials and procedures in civil construction in each country. In the second study, knowing that the material present in the hollow concrete blocks has, due to its geometry and manufacturing process, intrinsic properties that differ from the wet cast concrete material, a methodology is developed to evaluate and obtain, in laboratory, of the mechanical resistance of concrete blocks under high temperatures in a more adequate way. Then, in a third study, the thermal and physical properties of dry vibrated concrete, consisting of different types of coarse aggregate (basalt, limestone, and gneiss) and three different strength classes of blocks (6, 12 and 24 MPa) are investigated; comparing and evaluating the similarities and differences with wet cast concrete. The particularities of dry concrete used in the manufacture of masonry blocks showed significant differences in some analyzes due to their peculiarities in terms of porosity, humidity, density, etc. Based on the methodology properly developed to evaluate hollow concrete blocks, a fourth study was carried out to evaluate the influence that the type of coarse aggregate and the resistance class of the blocks, after heating, exert on the residual mechanical strength. It was observed that the mechanical behavior of hollow concrete blocks differs, to a certain degree, from the residual mechanical behavior found in the literature for wet cast concrete. Hollow concrete blocks tend to maintain compressive strength from room temperature to higher temperatures, 300°C for siliceous aggregates and 400°C for limestone aggregates. With the parameters obtained in the previous phases of the study, which served as a starting point in the approach of thermal models, in the fifth study, it was possible to determine isotherms of the concrete blocks by numerical models calibrated from experimental results. In this way, a numerical approach to verify in a simplified way the resistance of concrete blocks in fire situation by analytical method is presented. The data and analyzes reported on methodology, residual thermal and mechanical properties of hollow concrete blocks produced from a concrete mixture of very dry consistency, vibro-pressed and with normal weight aggregates, are new and unprecedented to enable the understanding of the behavior of Brazilian blocks and guide future research.
Behavior of structural concrete blocks with different aggregates under high temperatures
Keywords: Elevadas temperaturas; Alvenaria estrutural; Blocos de concreto; Análise experimental; Abordagem numérica; High temperatures; Structural masonry; Concrete blocks; Experimental analysis; Numerical analysis; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS